Symmetry-breaking cilia-driven flow in embryogenesis - Smith, David J. (2022)
Funding Information: D.J.S. acknowledges funding from an Engineering and Physical Sciences Research Council (EPSRC) Healthcare Technologies Challenge Award (EP/N021096/1); D.J.S. and T.D.M.-J. acknowledge funding from EPSRC First Grant EP/K007637/1. T.D.M.-J. acknowledges a Royal Commission for the Exhibition of 1851 Research Fellowship. S.S.L. acknowledges funding from Fundação para a Ciência e a Tecnologia (FCT-ANR/BEX-BID/0153/2012 research grant) and FCT Investigator award IF/00951/2012. We are particularly grateful for the guidance and encouragement of Professor Julyan Cartwright and the late Professor John Blake. We thank colleagues Dr. Adan Guerrero and ´ Dr. Idan Tuval and current and former members of the Lisbon and Birmingham groups for their valuable contributions.